Tính:
(2x+3)2
Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
\(\left(2x+3\right)^2+\left(2x-3\right)^2-2\left(2x+3\right)\left(2x-3\right)\)
\(=\left(2x+3-2x+3\right)^2\)
\(=9^2\)
\(=81\)
\(\left(2x+3\right)^2+\left(2x-3\right)^2-2\left(2x+3\right)\left(2x-3\right)\)
\(=\left(2x+3\right)^2-2\left(2x+3\right)\left(2x-3\right)+\left(2x-3\right)^2\)
\(=\left(2x+3-2x+3\right)^2\)
\(=6^2=36\)
\(A=\dfrac{2tan^2a+\dfrac{5}{cos^2a}}{4-\dfrac{3}{cos^2a}}=\dfrac{2tan^2a+5\left(1+tan^2a\right)}{4-3\left(1+tan^2a\right)}=...\) (bạn tự thay số bấm máy nhé)
\(B=\dfrac{3cot^2a-1}{cot^2a+2}=...\)
Ta có: \(\left(2x+3\right)^2+\left(2x+5\right)^2-2\left(2x+3\right)\left(2x+5\right)\)
\(=\left(2x+3-2x-5\right)^2\)
\(=\left(-2\right)^2=4\)
1) `2x(3x-1)-(2x+1)(x-3)`
`=6x^2-2x-2x^2+6x-x+3`
`=4x^2+3x+3`
2) `3(x^2-3x)-(4x+2)(x-1)`
`=3x^2-9x-4x^2+4x-2x+2`
`=-x^2-7x+2`
3) `3x(x-5)-(x-2)^2-(2x+3)(2x-3)`
`=3x^2-15x-(x^2-4x+4)-(4x^2-9)`
`=3x^2-15x-x^2+4x-4-4x^2+9`
`=-2x^2-11x+5`
4) `(2x-3)^2+(2x-1)(x+4)`
`=4x^2-12x+9+2x^2+8x-x-4`
`=6x^2-5x+5`
a, \(A=\dfrac{3sin^2\left(x\right)-cos^2\left(x\right)}{2sin^2\left(x\right)}=\dfrac{3}{2}-\dfrac{1}{2}\dfrac{cos^2\left(x\right)}{sin^2\left(x\right)}=\dfrac{3}{2}-\dfrac{1}{2}\cdot\dfrac{1}{tan^2\left(x\right)}=\dfrac{3}{2}-\dfrac{1}{2}\cdot\left(-\dfrac{3}{2}\right)^2=-3\)
b, \(A=\dfrac{sin^2\left(x\right)-5cos^2\left(x\right)}{2cos^2\left(x\right)}=\dfrac{1}{2}\dfrac{sin^2\left(x\right)}{cos^2\left(x\right)}-\dfrac{5}{2}=\dfrac{1}{2}\cdot\dfrac{1}{cot^2\left(x\right)}-\dfrac{5}{2}=\dfrac{1}{2}\cdot\left(\dfrac{5}{3}\right)^2-\dfrac{5}{2}=\dfrac{55}{18}\)
Lời giải:
a.
\(A=\frac{3}{2}-2(\frac{\cos x}{\sin x})^2=\frac{3}{2}-2.(\frac{1}{\tan x})^2=\frac{3}{2}-\frac{1}{2}(\frac{-3}{2})^2=-3\)
b.
\(A=\frac{1}{2}(\frac{\sin x}{\cos x})^2-\frac{5}{2}=2(\frac{1}{\cot x})^2-\frac{5}{2}=2(\frac{5}{3})^2-\frac{5}{2}=\frac{55}{18}\)
a) 3x3(2x2-7x+2)=6x5-21x4+6x3.
b) (2x2-3x)(2x+3)=4x3+6x2-6x2-9x=4x3-9x.
\(\left(2x-3\right)\left(2x+3\right)-\left(2x-1\right)^2\)
\(=\left(4x^2-9\right)-\left(2x-1\right)^2\)
\(=4x^2-9-\left(4x^2-4x+1\right)\)
\(=4x^2-9-4x^2+4x-1\)
\(=4x-10\)
a) (2x+1)^2-2(2x+1)(2x-1)+(2x-1)^2
=(2x+1-2x+1)^2
=2^2=4
b)\(\left(2x^3-3x^2+6x-9\right)\left(2x-3\right)\)
\(=\left[x^2\left(2x-3\right)+x\left(2x-3\right)\right]\left(2x-3\right)\)
\(=\left(2x-3\right)\left(x^2+x\right)\left(2x-3\right)\)
\(=\left(2x-3\right)^2\left(x^2+x\right)\)
tự làm tiếp đi nha
\(2x^3+5c^3=2x^3+5x^3\)
\(7x^2\left(2x^3+3x^5\right)=7x^2\cdot2x^3+7x^2\cdot3x^5=14x^5+21x^7\)
\(\dfrac{\left(x^3y^2-2x^2-3x^3+xy^4\right)}{xy^2}\)
\(=\dfrac{xy^2\cdot x^2-x\cdot2x-x\cdot3x^2+xy^2\cdot y^2}{xy^2}\)
\(=x^2-\dfrac{2x}{y^2}-\dfrac{3x^2}{y^2}+y^2\)
Lời giải:
a.
$5x-[2x+1-(2x-3)-(4x+1)]=5x-(2x+1-2x+3-4x-1)$
$=5x-(-4x+3)=5x+4x-3=9x-3$
b.
$(-3x^2+2x-1)+(4x^2-2x+3)$
$=-3x^2+2x-1+4x^2-2x+3=x^2+2$
( 2x + 3 )2
= ( 2x + 3 ) . ( 2x + 3 )
= 2x2 + 6x + 6x + 3
= 2x2 + 12x + 3
\(\left(2x+3\right)^2\)
\(=2x^2+2.2x.3+3^2\)
\(=2x^2+12x+9\)